Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.4028/www.scientific.net/amm.193-194.683
|View full text |Cite
|
Sign up to set email alerts
|

Study of Simulation in Storm Sewer System of Zhenjiang Urban by Infoworks ICM Model

Abstract: Through a typical rainstorm process, the rainwater outlet amount and the catchment area of Zhenjiang urban is collected. It is simulated by Infoworks ICM model, the corresponding parameters of substitution are applied. The results found: The model can better reflect heavy rain or rainstorm of rainwater outlet catchment case of Zhenjiang urban.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It reveals that machine learning technology has unique advantages (higher computation speed, lesser data requirements, and more robust results) in rapid damage assessment and has been paid attention to by relevant researchers. Moreover, the access cycles of remote sensing technology are long because of the limitation of low spatiotemporal resolution of data and lack of easy satellite due to cloud obscuration [67][68][69][70]. However, urban floods are often of short duration, requiring high-temporal-resolution data [71].…”
Section: Recommendation 4: Response Functionsmentioning
confidence: 99%
“…It reveals that machine learning technology has unique advantages (higher computation speed, lesser data requirements, and more robust results) in rapid damage assessment and has been paid attention to by relevant researchers. Moreover, the access cycles of remote sensing technology are long because of the limitation of low spatiotemporal resolution of data and lack of easy satellite due to cloud obscuration [67][68][69][70]. However, urban floods are often of short duration, requiring high-temporal-resolution data [71].…”
Section: Recommendation 4: Response Functionsmentioning
confidence: 99%
“…InfoWorks Integrated Catchment Modeling (ICM) is among the flood models that integrate GIS interface to provide a comprehensive range of applications. Due to its pre-and post-processing capacities, InfoWorks ICM is widely used for integrated catchment modeling [18][19][20][21][22][23] and flood hazard and risk mapping studies [24][25][26][27][28]. In recent decades, there has been a growing demand for flood models that have a high reliability to produce as much of a near-real-time flood scenario as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Common urban rainstorm models include SWMM, MIKE Urban, InfoWorks ICM, and TEMEMAC-2D, etc. [26][27][28][29]. In this study, the TELEMAC-SWMM coupled model was selected to simulate urban flooding under the following considerations: (1) After decades of development and research, the EXTRAN module and the TELEMAC-2D module have shown strong performance in the fields of one-and two-dimensional hydrodynamics.…”
Section: Introductionmentioning
confidence: 99%